Peran Pemerintah Daerah Dalam Melestarikan Situs Budaya (Studi Kasus Petilasan Tribuana Tungga dewi di desa Klinterejo Kecamatan Sooko Kabupaten Mojokerto) - M. Ridlo Habibi; Machwal Huda; Nieke Rudyanty Winanda (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Mojokerto Regency is one of the areas in East Java which has historical heritage. It is not surprising that the district has many historical relics, such as the Petilasan Tribuana Tunggadewi in Klinterjo Village, Sooko District, Mojokerto Regency. This study uses a qualitative method. Technical analysis of this data using descriptive qualitative. The data collection technique uses the snowball method with four informants. Source of data obtained based on primary data and secondary data. To collect data researchers used observation techniques, in-depth interviews, and documentation. The data analysis model used is data collection, data reduction, data presentation, and drawing conclusions. This study aims to determine the form of the role of local governments in preserving cultural sites up to their utilization and also to determine the supporting and inhibiting factors in preserving cultural sites. The results of this study indicate that there are several stakeholders who are responsible for preserving the Tribuana Tunggadewi ruins, where the Tribuana Tunggadewi ruins are included in the National Cultural Heritage Area (KCBN). This is what plays an important role in the preservation of the ministry, this has been regulated in the Cultural Heritage Law No. 10 of 2011. As is the case in excavations where this is carried out by the East Java Region XI Cultural Preservation Center (BPK) under the supervision of the ministry, this makes the Mojokerto district government in its utilization was hindered by regulations from the ministry, but the existence of this partition did not make the role of the Mojokerto district government hands off as a regulator such as outreach to the residents of Klinterjo village in collaboration with the local village government and also from BPK region XI East Java. While the facilitator is like in making roads leading to the petilasan area or supporting facilities such as building a prayer room in the petilasan area, toilets, and the pavilion. From the results of this study it can be concluded that the preservation of the Tribuana Tunggadewi ruins has stakeholders who oversee the preservation of cultural heritage, both from the central, district and village governments.